Hâ Estimation Approach to Active Noise Control: Theory, Algorithm and Real-Time Implementation - Bambang Riyanto (Journal of Engineering and Technological Sciences, 2003)
This paper presents an Hâ estimation approach to active control of acoustic noise inside an enclosure. It is shown how Hâ filter theory and algorithm can be effectively applied to active noise control to provide important robustness property. Real-time implementation of the algorithm is performed on Digital Signal Processor. Experimental comparison to conventional FxLMS algorithm for active noise control is presented for both single channel and multichannel cases. While providing some new results, this paper also serves as a brief review on Hâ filter theory and on active noise control.